The Anti-Cancer Mechanisms of Berberine: A Review - Wang, Ye; Liu, Yanfang; Du, Xinyang; Ma, Hong; Yao, Jing (Cancer management and research, 2020)
Berberine (BBR) has been extensively studied in vivo and vitro experiments. BBR inhibits cell proliferation by regulating cell cycle and cell autophagy, and promoting cell apoptosis. BBR also inhibits cell invasion and metastasis by suppressing EMT and down-regulating the expression of metastasis-related proteins and signaling pathways. In addition, BBR inhibits cell proliferation by interacting with microRNAs and suppressing telomerase activity. BBR exerts its anti-inflammation and antioxidant properties, and also regulates tumor microenvironment. This review emphasized that BBR as a potential anti-inflammation and antioxidant agent, also as an effective immunomodulator, is expected to be widely used in clinic for cancer therapy.